2008
DOI: 10.2516/ogst:2008010
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Charge Compression Ignition: Formulation Effect of a Diesel Fuel on the Initiation and the Combustion - Potential of Olefin Impact in a Diesel Base Fuel

Abstract: Résumé -Combustion en mode HCCI : impact de la formulation d'un carburant Diesel sur l'initiation et la combustion -Potentiel de l'ajout d'oléfine dans une base gazole -L'objectif de ce travail est de proposer une amélioration du contrôle et de l'initiation de la combustion en mode HCCI via la formulation du carburant. L'article présente l'impact de l'addition d'oléfines (et en particulier l'addition de 1-octène et d'octa-1,7-diène) dans une base gazole. Les tests sont effectués à l'aide d'un réacteur auto-agi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…However, the knowledge on the kinetics of the oxidation of alkenes is limited compared to that for alkanes. Several studies have been reported for the development of a detailed kinetic mechanism for alkene combustion [1][2][3][4] based mostly on analogy to the mechanism of the combustion of alkanes, by taking into account the stability of allyl and substituted allyl radicals which seem to be the most characteristic difference from the alkane oxidation. An extensive quantum chemical investigation has been reported for the reaction of allyl (C 3 H 5 ) radicals with O 2 [5], which is a prototypical oxidation step of alkenes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the knowledge on the kinetics of the oxidation of alkenes is limited compared to that for alkanes. Several studies have been reported for the development of a detailed kinetic mechanism for alkene combustion [1][2][3][4] based mostly on analogy to the mechanism of the combustion of alkanes, by taking into account the stability of allyl and substituted allyl radicals which seem to be the most characteristic difference from the alkane oxidation. An extensive quantum chemical investigation has been reported for the reaction of allyl (C 3 H 5 ) radicals with O 2 [5], which is a prototypical oxidation step of alkenes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the olefin content increase and the cetane number decreases as the proportion of TDF in the fuel blend increases. Increased olefin content reduces the physical ignition delay and increases the chemical ignition delay due to olefin chemistry explained in detail in Ref [23]. The reduced cetane number of TDF blends also prolongs the chemical ignition delay and the total effect of the above-mentioned factors leads to the TDF blend having a longer ignition delay.…”
Section: Figure 2 Comparison Of Ignition Delay Periodmentioning
confidence: 95%
“…The lower the distillation range and flash point, the higher the fuel volatility. In addition, the higher olefin content of fuel decreases the temperature of the distillation range, makes the fuel more evaporative, leads to greater heat absorption from the combustion chamber, and results in a delay in the combustion process [23]. The hydrocarbon composition of fuels such as aromatic and olefin content affects the cetane number.…”
Section: Fuel Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely agreed that presence of olefins affects the quality of Diesel fuels as well [4,5], due to their relatively low cetane numbers [6] and smoke points [7]. At the same time, Alseda et al [8] have demonstrated the advantage of the light olefins addition in Diesel fuels. Furthermore, C 10 -C 18 olefins such as 1-dodecene or 1-tetradecene meet viscosity and pour points specifications for formulation into oil based muds and exhibit good biodegradability while being non-toxic to marine organisms and less irritating to skin than many alternatives.…”
Section: Introductionmentioning
confidence: 98%